Molecular nutrition - Daniel, Hannelore; Zempleni, Janos (CABI Publishing, 2003)
This book contains 24 chapters covering a broad range of research in molecular nutrition. The first 2 chapters by J. Zhang and H. Daniel cover technical advances that have been made in genomics and post-genomics, and the promise that these technologies ld for future nutrition research. Next, H. Daniel, D.B. McCormick and J. Zempleni tell us how nutrients enter cells, how they are being targeted to their sites of action in cells and how physiological processes such as cell proliferation affect nutrient transport. This section is completed by a chapter by J.C. Mathers in which he reviews the roles for nutrients in apoptosis. A series of fine chapters by F. Foufelle and P. Ferr??e, M.S. Kilberg et al., U. Beisiegel et al., D.R. Soprano and K.J. Soprano, K. Dakshinamurti, A. Fischer et al., E.M. Schmelz, T. Badger et al., and D. Attaix et al. provides examples for roles of macro- and micronutrients in signal transduction, gene expression and proteolysis. J.K. Christman, J. Zempleni, and J. Kirkland and J.C. Spronck contributed reviews of nutrient-dependent modifications of nucleic acids and nucleic acid-binding proteins. Chapters on regulation of lipoprotein assembly (J.A. Higgins), cellular cholesterol metabolism (J.-Y. Lee et al.), oxidative stress (A. Taylor and M. Siegal) and immune function (P. Yaqoob and P.C. Calder) were selected to demonstrate how events at the molecular level can be integrated into multiorgan and whole-body metabolic pathways. Finally, J.S. Stanley and G. Bannon, and S.L. Taylor share their thoughts in the fields of genetically modified foods and molecular mechanisms of food allergy.